"'As I said to you before': Paul's witness to formative early Christian instruction - Edsall, B (2013)
This study addresses the question of formative early Christian preaching and teaching. Unlike previous approaches, I eschew synthesis across a broad range and focus instead on the earliest extant Christian source: the letters of Paul. My method draws on ancient communication practices, primarily represented in ancient rhetoric, wherein communicators rely on knowledge they presume their interlocutors to possess. Passages are analyzed according to the type of appeal to Paul's initial teaching: (1) explicit reminders of previous teaching, (2) direct appeals to knowledge not explicitly linked to previous teaching, and (3) indirect appeals to knowledge about practices, beliefs, conventions, etc. The reconstruction focuses on 1 Thessalonians, 1 Corinthians and Romans. 1 Thessalonians and 1 Corinthians represent neophyte and well-established Pauline communities, respectively, while Romans is of interest because it represents non-Pauline believers. I proceed with a comparative analysis of 1 Thessalonians and 1 Corinthians. Chapter 4 lays out the rhetorical situation for these letters while chapters 5-7 investigate the three types of appeal respectively, each closing with a comparison of similar material in each letter. Chapter 8 summarizes and concludes this discussion, providing the basis for my subsequent analysis of Romans. Finally, I compare the picture from the Thessalonian and Corinthian communities with Paul's letter to the Romans (chapter 9). Topics he expects his Roman audience to know indicate points of expected congruence between Paul's own teaching and that of others. By contrast, topics that receive significant expansion in Romans suggest perceived potential for conflict. In this dissertation I identify consistent elements of early Christian instruction, ranging from Christology to apocalyptic cosmology, while also noting possible conflict. My approach places the reconstruction of early Christian teaching on firmer methodological footing than previous attempts have done and offers a rhetorically sensitive account of the teaching and how it was used.